Fiduciary Guarantee Registration Implementation Through Electronic (Online System) in Indonesia - Satory, Agus; Ahmad, Sufmi Dasco; Nugraha, Roby Satya (JURNAL AKTA, 2024)
The aim of this research is to analyze the implementation of electronic fiduciary registration in Indonesia and to analyze the factors that support and hinder the implementation of electronic fiduciary registration. The research methods taken in this study is a normative juridical approach supported by empirical data. Fiduciary as a guarantee institution is regulated in Law No. 42 of 1999 concerning Fiduciary Guarantees and followed up with Government Regulation Number 21 of 2015 concerning Procedures for Registration of Fiduciary Guarantees and Costs for Making Fiduciary Guarantee Deeds. Fiduciary registration cannot be separated from fiduciary collateral because fiduciary registration results in guaranteed legal certainty for creditors and interested parties. However, until now there are still many fiduciary guarantees that are not registered because many things have become obstacles in the registration process for fiduciary guarantees. To overcome the obstacles that occur in daily practice both those that occur in bank financing institutions and non-bank financing institutions (leasing) and notaries in registration of fiduciary guarantees, then the government made a new breakthrough by increasing the service of registration of fiduciary guarantees easily, quickly, and at low cost, namely by conducting electronic fiduciary registration services.